Efek Pairing Pada Isotop Zr dengan Potensial Interaksi Uniform 0.5 MeV - Mahisha Nugraha, Alpi; Nurullaeli, Nurullaeli (Jurnal Jejaring Matematika dan Sains, 2021)
Pairing effect is a collective phenomenon in many body (fermion) nuclei, pairs of fermions will form a nucleon (boson) condition which is will decrease of the binding energy of nuclei (more negatively). One tool to see that in Zr-isotopes is using Relativistic Mean Field (RMF) model with combined BCS-theoretical. The pairing effect also represents of total interaction that occurs in outermost level nuclei after closed shell as 40Zr90. Those level are 2d5/2, 1g7/2, 3s1/2, 2d3/2, and 4s1/2. Effect pairing depending by matrix potential interaction which is in this paper we used uniform potential interaction 0.5 MeV. However, to obtain more accurate results, other methods to minimize the differences with the experimental results are clearly needed here.